Solid pseudopapillary tumor of the pancreas. An unusual presentation (Revista Argentina de Cirugía, 2021)
The pseudopapillary solid tumors of the pancreas are a rare entity of which cell origin is unknown. Its solid papillary cystic feature is due to the formation of a solid tumor with areas of necrobiotic degeneration due to lack of vascularization. Its symptoms are nonspecific, with compression and dilation of the main biliary tract with the onset of obstructive jaundice uncommon. Differential diagnoses include solid and cystic tumors. The treatment of choice is resective surgery with oncologic criteria.
Keywords: pancreas; solid pseudopapillary tumors; dilatation of biliary tract; jaundice; duodenopancratectomy